التنظيم القانوني لاستخدام الأنهار الدولية للأغراض غير الملاحية - جامع شادي (Latakia University Journal - Economic and Legal Sciences Series, 2016)
Water is an important source and vital for human life and especially in light of the large population growth and lack of water resource in the Middle East, so it knows the international community the importance of the water issue and the adoption of an international treaty under the auspices of the United Nations related to international rivers for purposes of non-navigation, we will discuss in our search the study of the most important principles endorsed by this agreement as a principle of fair use and equitable, and the principle of the obligation not to cause harm to other countries, in addition to display procedures Almtojb followed during the use of international rivers for purposes other than navigation, with link this topic to the status of the Euphrates River as a case process and especially in light of the government’s refusal Turkey’s signing of the Treaty, and mind that the Euphrates River is an internal river is not subject to international principles of sharing water. تعتبر المياه مصدرا مهما و حيويا للحياة الإنسانية في ظل التزايد السكاني الكبير, و نقص مورد المياه في منطقة الشرق الأوسط. لذلك أدرك المجتمع الدولي أهمية المسألة المائية و قام بتبني معاهدة دولية تحت اشرف الأمم المتحدة متعلقة بالأنهار الدولية للإغراض غير الملاحية. سنتناول في بحثنا دراسة أهم المبادئ التي أقرتها هذه الاتفاقية كمبدأ الاستخدام العادل و المنصف, و مبدأ الالتزام بعدم التسبب بضرر للدول الأخرى, بالإضافة لعرض الإجراءات المتوجب إتباعها أثناء استخدام الأنهار الدولية للأغراض غير الملاحية مع ربط هذا الموضوع بحالة نهر الفرات بوصفه حالة عملية و خاصة في ظل رفض الحكومة التركية التوقيع على المعاهدة المذكورة و اعتبار أن نهر الفرات هو نهر داخلي لا يخضع للمبادئ الدولية لاقتسام المياه.